Knowledge, attitude, and practice of healthcare workers of primary health facilities of Kathmandu district, Nepal on infection prevention and control - Bhandari, Karuna; Bista, Pariwesh Raj; Koirala, Sita; Shah, Archana; Shrestha, Binjwala (International Journal of Infection Control, 2025)
Introduction: Primary healthcare facilities are the first point of contact for the utilization of healthcare services. Adopting appropriate infection prevention and control (IPC) measures helps to control the emergence and spread of infection in the community. No study related to the knowledge, attitude, and practice of healthcare workers (HCWs) on IPC was done at the primary health facility level till the date of this study. Aim: To assess the knowledge, attitudes, and infection control practices among Nepalese HCWs working in primary health facilities. Methods: This was a descriptive cross-sectional study conducted among 156 health workers from municipalities of the Kathmandu district. Multistage simple random sampling was used in which five municipalities were selected randomly and health workers were selected proportionately afterward. Results: Out of the total participants, more than half of them had not obtained infection control training. Only 15.4 3.2, and 10.3% of the respondents achieved maximum scores for knowledge, attitude, and practice items, respectively. Although staff had good knowledge and a positive attitude towards most aspects of infection control, nearly two-thirds (62.8%) of the participants had not heard about methicillin-resistant Staphylococcus aureus. Conclusion: There was an irregular supply of basic supplies such as masks, gloves, aprons, supply of water, hand-washing basins, soap, and hand sanitizer. Therefore, every local level should equip all health facilities of its catchment area with the basic supplies as listed in the Minimum Service Standard guideline for the correct application of IPC.